BEDMAP2 - Ice thickness, bed and surface elevation for Antarctica - standardised data points ... - Fretwell, Peter; Fremand, Alice; Bodart, Julien; Pritchard, Hamish; Vaughan, David; Bamber, Jonathan; Barrand, N.; Bell, R.E.; Bianchi, C; Bingham, Robert; Blankenship, Donald; Casassa, G.; et al. (NERC EDS UK Polar Data Centre, 2022)
We present here the Bedmap2 ice thickness, bed and surface elevation standardised CSV data points that were used to create the Bedmap2 gridding products. The data consists of 25 million points coming from 68 individual surveys acquired in Antarctica. The associated datasets consist of: - Bedmap1 standardised CSV data points: https://doi.org/10.5285/f64815ec-4077-4432-9f55-0ce230f46029 - Bedmap3 standardised CSV data points: https://doi.org/10.5285/91523ff9-d621-46b3-87f7-ffb6efcd1847 - Bedmap2 statistically-summarised data points (shapefiles): https://doi.org/10.5285/0f90d926-99ce-43c9-b536-0c7791d1728b - Bedmap2 gridding products: https://doi.org/10.5285/fa5d606c-dc95-47ee-9016-7a82e446f2f2 This work is supported by the SCAR Bedmap project and the British Antarctic Survey's core programme: National Capability - Polar Expertise Supporting UK Research ... : The primary source data consist of survey point measurements of ice thickness, bed elevation and surface elevation, which principally comes from airborne radar surveys and seismic soundings, and to a smaller extent from ground-based radar surveys. All the data have been standardised to a specific CSV format. The format consists of (i) an extended header section where (a) each line is introduced by a comment ("#") character, (b) each line contains a single header item, (c) the colon character (":") is used as the key/value separator, (d) units are in parentheses, (e) attributes preferably use a common vocabulary such as the CF convention and includes attributes from the ACDD; (ii) a header row composed of the column name following the CF convention and units in parentheses; and finally (iii) the data using comma as the separator. The extended header consists of general information regarding each campaign such as the year, the name of the main investigator, funding and processing details. The variable names ...